Perencanaan Strategis Sistem Informasi Menggunakan Metode Anita Cassidy (Studi Kasus: CV. Putra Bintang Api) - Setiono, Tegar; Cahyono, Ariya Dwika (STMIK Banjarbaru, 2026)
This research aims to develop a Strategic Information System Plan for CV. Putra Bintang Api, a building material trading company that still faces limitations in its information system in supporting operations and decision-making. The Anita Cassidy method was employed because it provides a phased approach through the visioning, analysis, direction, and recommendation stages to ensure alignment between the business strategy and the company's IS/IT requirements. Value Chain analysis, Porter's Five Forces, SWOT, and the IFAS and EFAS matrices were conducted to evaluate the company's internal and external conditions. The research findings result in a three-year information system development Roadmap which includes ERP implementation, POS system upgrade, official website development, CRM implementation, and the digitalization of internal processes. The roadmap is complemented by budget estimations and ROI calculations, providing a measurable basis for decision-making. This planning is expected to significantly enhance efficiency, data integration, and the company's competitiveness in the digital era. Keywords; Information System Strategic Planning; Anita Cassidy; IS/IT Roadmap; CV. Putra Bintang ApiAbstrakPenelitian ini bertujuan menyusun perencanaan strategis sistem informasi pada CV. Putra Bintang Api, sebuah perusahaan dagang bahan bangunan yang masih menghadapi keterbatasan sistem informasi dalam mendukung operasional dan pengambilan keputusan. Metode Anita Cassidy digunakan karena menyediakan pendekatan bertahap melalui fase visioning, analysis, direction, dan recommendation untuk memastikan keselarasan antara strategi bisnis dan kebutuhan SI/TI. Analisis Value Chain, Porter Five Forces, SWOT, serta matriks IFAS dan EFAS dilakukan untuk mengevaluasi kondisi internal dan eksternal perusahaan. Hasil penelitian menghasilkan roadmap pengembangan sistem informasi selama tiga tahun yang mencakup implementasi ERP, peningkatan POS, pembangunan website, penerapan CRM, dan digitalisasi proses internal. Roadmap dilengkapi estimasi anggaran dan perhitungan ROI sehingga memberikan dasar pengambilan keputusan yang terukur. Perencanaan ini diharapkan mampu meningkatkan efisiensi, integrasi data, serta daya saing perusahaan di era digital.